Respuesta :
1. I suppose the ODE is supposed to be
[tex]\mathrm dt\dfrac{y+y^{1/2}}{1-t}=\mathrm dy(t+1)[/tex]
Solving for [tex]\dfrac{\mathrm dy}{\mathrm dt}[/tex] gives
[tex]\dfrac{\mathrm dy}{\mathrm dt}=\dfrac{y+y^{1/2}}{1-t^2}[/tex]
which is undefined when [tex]t=\pm1[/tex]. The interval of validity depends on what your initial value is. In this case, it's [tex]t=-\dfrac12[/tex], so the largest interval on which a solution can exist is [tex]-1\le t\le1[/tex].
2. Separating the variables gives
[tex]\dfrac{\mathrm dy}{y+y^{1/2}}=\dfrac{\mathrm dt}{1-t^2}[/tex]
Integrate both sides. On the left, we have
[tex]\displaystyle\int\frac{\mathrm dy}{y^{1/2}(y^{1/2}+1)}=2\int\frac{\mathrm dz}{z+1}[/tex]
where we substituted [tex]z=y^{1/2}[/tex] - or [tex]z^2=y[/tex] - and [tex]2z\,\mathrm dz=\mathrm dy[/tex] - or [tex]\mathrm dz=\dfrac{\mathrm dy}{2y^{1/2}}[/tex].
[tex]\displaystyle\int\frac{\mathrm dy}{y^{1/2}(y^{1/2}+1)}=2\ln|z+1|=2\ln(y^{1/2}+1)[/tex]
On the right, we have
[tex]\dfrac1{1-t^2}=\dfrac12\left(\dfrac1{1-t}+\dfrac1{1+t}\right)[/tex]
[tex]\displaystyle\int\frac{\mathrm dt}{1-t^2}=\dfrac12(\ln|1-t|+\ln|1+t|)+C=\ln(1-t^2)^{1/2}+C[/tex]
So
[tex]2\ln(y^{1/2}+1)=\ln(1-t^2)^{1/2}+C[/tex]
[tex]\ln(y^{1/2}+1)=\dfrac12\ln(1-t^2)^{1/2}+C[/tex]
[tex]y^{1/2}+1=e^{\ln(1-t^2)^{1/4}+C}[/tex]
[tex]y^{1/2}=C(1-t^2)^{1/4}-1[/tex]
I'll leave the solution in this form for now to make solving for [tex]C[/tex] easier. Given that [tex]y\left(-\dfrac12\right)=1[/tex], we get
[tex]1^{1/2}=C\left(1-\left(-\dfrac12\right)^2\right))^{1/4}-1[/tex]
[tex]2=C\left(\dfrac54\right)^{1/4}[/tex]
[tex]C=2\left(\dfrac45\right)^{1/4}[/tex]
and so our solution is
[tex]\boxed{y(t)=\left(2\left(\dfrac45-\dfrac45t^2\right)^{1/4}-1\right)^2}[/tex]